Características de estrutura de personalidade de pais, mães e crianças envolvidas no fenômeno da Alienação Parental - Damiani, Fabiana da Motta (Universidade do Vale do Rio dos Sinos, 2012)
The Parental Alienation phenomenon has been observed in close relationship with highly conflicting divorces. Parental Alienation is characterized by one parent pushing children away from the other parent without an apparent or real justification. (Darnall, 1997; Gardner, 1987). Children adopt a repulsion behavior, keeping a close bond to the alienating parent and disqualifying the alienated parent. According to IBGE (Brazilian Statistics and Geography Institute) the number of divorce and separations has been increasing in Brazil. There was a 59,6% increase in these numbers from 1991 to 2002 (IBGE, 2002/2003). This reality shows that the number of children and adolescents involved in family conflicts is also rising. Research in the field highlights this is a dynamic process which involves all members in the nuclear family. However, the way in which each family member participates in the conflict is yet to be made clear. The objective of the present study is to analyze and understand the personality structure traits of the mothers, fathers and children involved in the Parental Alienation phenomenon. Having this objective in mind, a qualitative-exploratory approach was used in the present research along with a case study procedure. The results showed alienating mothers as having unstable personality traits and symbiotic, fragile bonding which is subject to rupture. It was also possible to observe primitive defenses and intense separation anxiety. These results point to traits that are compatible with borderline personality organizations. Alienated parents showed depression, feelings of hopelessness and immaturity traits. Concerning the children, the results showed children with a more regressive psychodynamic functioning, dependency traits and feelings such as fear, loneliness and sadness. The results were organized in two empirical studies: the first one discusses the personality structure traits of both fathers and mothers involved in the Parental Alienation 7 phenomenon; and the second article shows the psychodynamic functioning characteristics of the children involved in the Parental Alienation phenomenon.
Keywords: Alienação Parental; Divórcio; Personalidade; Parental Alienation; Divorce; Personality; ACCNPQ::Ciências Humanas::Psicologia